GEROFIT PREHABILITATION TO IMPROVE POST-OPERATIVE OUTCOMES IN AN OLDER/AT-RISK POPULATION. (11th November 2018) - Andonian, N; Lee, C C; Blanchard, E; Roberts, C; Singh, S; Russell, M; Bojalian, M; Castle, S C
Abstract: Background. More than 1/3 of surgeries are done in those 65+, with increased complications, length of stay (LOS) and readmissions. Preoperative rehabilitation (prehab) is designed to both optimize patient fitness and mental preparedness for surgery. Methods. For the Gerofit program, fitness assessments are done to individualize a 4–8 week prehab exercise program (cardio, strength, balance & inspiratory muscle training) and discuss potential complications using the National Surgical Quality Improvement Program (NSQIP) Risk Calculator. Results. Nine patients, mean 73.2 + 5.3 years with 2.2 'trigger factors' (ADL/IADL assistance, high comorbidity, decline in vision, hearing or cognition, chronic opioids and PTSD) completed a mean 18 + 8 prehab workouts. Actual LOS is 0.5 + 2.3 days longer than NSQIP expected LOS. There was one complication and one 30-day readmission. Implications. We intend to use this multidisciplinary platform to develop effective/user friendly frailty screening, fitness optimization and care/transition coordination to develop high quality perioperative management of older, at-risk adults.